PENINGKATAN DAYA SAING USAHA OLAHAN PANGAN (PEYEK KACANG DAN EMPING MELINJO) - Rita Kusumawati; Taufik Akhbar; Alien Akmalia (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
This programe aims to help partners to be more independent and improve their business competitiveness. Business partners in this program are Peyek Bu Dalidjo and melinjo chips "Sari Melinjo" where located in Kamijoro. Kamijoro is located in Sendangsari Village, Pajangan sub-district, Bantul Regency, Yogyakarta. This hamlet is located ± 15 Km to the southwest of the city of Yogyakarta which is exactly 8 km west of the city of Bantul. The village of Kamijoro is located in the heart of the capital of the Pajangan sub-district. The livelihoods of the people of Kamijoro are quite diverse, not a few among the inhabitants of this hamlet who make a living as entrepreneurs, including both partners in this program.Problems faced by the two partners include: 1) limited marketing aspects; 2) An improper business nameplate; 3) unfavorable business financial administration. The results of this program are: 1) Peyek bu Dalidjo and melinjo chips “Sari Melinjo” have an attractive label design and packaging; 2) Both partners expand marketing strategies through online marketing media and offline media; 3) both partners have a proper business name board; 4) partners understand and are able to make business cash flow records